The The Relationship between Age-advanced Learners’ In-class Willingness to Communicate in English, Intrinsic Motivation, Classroom Environment and Teacher Immediacy—A Pilot Study - Anna Borkowska (Theory and Practice of Second Language Acquisition, 2022)
The article aims to scrutinize third agers’ in-class willingness to communicate (WTC) in English as well as to determine the relationship among WTC, intrinsic motivation, classroom environment, and teacher immediacy. The instrument adapted to this study was a questionnaire comprising biodata items, the in-class WTC tool (Peng & Woodrow, 2010), intrinsic motivation (Noels, Clément, & Pelletier, 2001), classroom environment (Fraser, Fisher, & McRobbie, 1996), and the teacher immediacy scale (Zhang & Oetzel, 2006). The data revealed that senior learners’ WTC was higher in meaning-focused than in form-focused activities. This finding indicates that the participants paid due attention to communicative interactions in English. Also, they were more eager to be actively involved in dyadic exercises as it might have given them a sense of security and confidence. It is noteworthy that intrinsic motivation turned out to be the strongest predictor of in-class WTC. The analysis showed that communication in English abroad and in-class was of paramount relevance for the informants. The older adults also underscored the fundamental role of the language instructor. In this respect, the students attached great importance to a non-threatening atmosphere, and the teacher’s personality traits, namely patience, professionalism, and empathy.